An evaluation of property markets in Southwestern Nigeria. Issue 3 (18th June 2018) - Abere, Chioma Oluwaseun; Ogunba, Olusegun Adebayo; Dugeri, Terzungwe Timothy
Abstract : Purpose: Studies on the maturity status of Sub-Saharan African property markets are scanty. The absence of such studies appear to have made African property markets – such as the Nigerian market – unattractive to foreign investors who require market information to assess the viability of proposed investments. The purpose of this paper is to explore the maturity status of selected city property markets in Southwestern Nigeria (i.e. markets in the capital cities of Lagos, Ibadan and Osogbo), with a view to providing information for enhanced property investment in Africa. Design/methodology/approach: The study adopted and expanded on property market maturity paradigms suggested by Keogh and D'Arcy (1994), Akinbogun et al. (2014 ) and Jones Lang LaSalle (2014) to measure the maturity status of the property markets in the Nigerian cities. The study investigated the maturity of three markets in Nigeria by scoring the stated views of a range of stakeholders (estate surveyors and valuers, public land administrators and financiers represented by commercial banks) across a range of ten indicators. The responses were classified by means of a five-point classification scale which expanded on the initial four-point scale developed by Dugeri (2011). Findings: The three property markets were found to exhibit varying maturity characteristics (with weighted mean scores of 3.07, 2.71 and 2.51, respectively), representing emerging and immature stages of evolution on the maturity path. These results suggest that there is a correlation between the tier of the market and the level of property market maturity. Practical implications: The study concluded that first- and second-tier city property markets have emerged sufficiently to the point where they may safely attract foreign direct and indirect investment from courageous foreign investors. However, the state governments and real estate professional regulatory bodies in the second and third markets need to undertake substantial remodeling of market structures to make them attractive to international investors. Originality/value: The value of the paper is in providing much needed information for enhanced property investment in Africa.